Understanding When Similarity-Induced Affective Attraction Predicts Willingness to Affiliate: An Attitude Strength Perspective - Philipp-Muller, Aviva; Wallace, Laura E.; Sawicki, Vanessa; Patton, Kathleen M.; Wegener, Duane T. (Frontiers in Psychology, 2020)
Individuals reliably feel more attracted to those with whom they share similar attitudes. However, this affective liking does not always predict affiliative behavior, such as pursuing a friendship. The present research examined factors that influence the extent to which similarity-based affective attraction increases willingness to affiliate (i.e., behavioral attraction) – one potential step toward engaging in affiliative behavior. Research on attitude strength has identified attitude properties, such as confidence, that predict when an attitude is likely to impact relevant outcomes. We propose that when one’s attitudes possess these attitude strength-related properties, affective attraction to those who share that attitude will be more likely to spark willingness to affiliate. Across four studies on a variety of topics, participants (N = 428) reported their attitudes and various attitude properties regarding a topic. They were introduced to a target and learned the target’s stance on the issue. Participants reported their affective attraction and willingness to pursue friendship with the target. Consistent with past research, attitude similarity predicted affective attraction. More importantly, the relation between affective attraction and willingness to affiliate with the target was moderated by the attitude strength-related properties. A mini meta-analysis found this effect to be consistent across the four studies.